Does Corporate Governance Matter, Evidence from Earnings Management Practices in Singapore - HU, Lingxu (Institutional Knowledge at Singapore Management University, 2010)
This paper addresses two questions. First, do good corporate governance practices add values to company or does it lead to higher stock returns in Singapore? Second, does poorly governed listed company in SGX tend to manage their earnings by using discretionary accruals? Following the approach of Gompers et al. (2003), we formed two portfolios consisting of well-governed and poorly governed companies. Well governed companies are able to maintain a higher return relative to poorly governed companies. I also look at the firm valuation from the adoption of corporate governance practices. Our result shows a positive relationship between firm valuation and corporate governance, we find Tobin’s Q to be significantly positively related to corporate governance. However, corporate governance does not necessarily improve firm’s performance. Finally, I also demonstrate that firm’s adoption of stringent corporate governance practices is associated with the magnitude of discretionary accruals, and limits discretion in earning management. Among different categories as prescribed by OECD, firms with best practices in the "Disclosure and transparency" category are associated with lower level of discretionary accruals.